Handbook of Lymphoma - Younes, Anas (Springer International Publishing : Imprint: Adis, 2016)
The Handbook of Lymphoma is an in-depth and comprehensive guide to the diagnosis, staging, treatment, and management of patients with the disease. The Handbook aims to provide healthcare professionals with an informative and up-to-date guide to the latest developments in the treatment of patients with both Hodgkin and non-Hodgkin lymphoma. Lymphoma is a cancer of the lymphatic system and, as with other cancers, is a disease of the body's cells. Usually, cells divide in the body in an orderly and controlled manner, however when this process gets out of control and the cells carry on dividing in an abnormal manner a tumor can form known as lymphoma in one or more groups of lymph nodes. This field has seen increasing development in the available options for treating patients with lymphoma particularly in the recent emergence and approval of targeted therapies. In this clinically focused Handbook, the authors address these advances by looking at treatment recommendations for both Hodgkin and non-Hodgkin lymphoma, and also making suggestions on the future outlook for patients with this disease. This Handbook is an invaluable and educational source of topical information for all medical and healthcare professionals with an interest in lymphoma.